The Impact of Macroprudential Policies on MSME Credit Growth and Risk - Ferry Fredrick Kaban; Dewi Hanggraeni (Dinasti Publisher, 2024)
The aim of this research is to identify the impact of macroprudential policy related to the financing ratio for micro small medium enterprises (MSME) to each bank’s MSME credit growth and non-performing loan (NPL). This research used a panel data analysis using the pooled least square (PLS) model conducted on the financial data of 40 public conventional banks for the observation during the period from 2012 to 2021 with MSME’s credit growth and NPL as the dependant variables and the policy, bank’s characteristics, and macroeconomic factors as independent variables. The results reveals that the policy significantly affects MSME’s credit growth and NPL. This study ultimately provides input for banks to fulfill the financing ratio in order to comply with the regulator but should be selective in terms of MSME’s financing. The findings of this research inquire regulator to re-evaluate the requirement target for all banks to achieve minimum financing MSME ratio.